2023
DOI: 10.1001/jamaoncol.2022.6901
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Age and Survival Trends in Advanced Non–Small Cell Lung Cancer After Adoption of Immunotherapy

Abstract: ImportanceThe introduction of immune checkpoint inhibitors (ICIs) has transformed the care of advanced non–small cell lung cancer (NSCLC). Although clinical trials suggest substantial survival benefits, it is unclear how outcomes have changed in clinical practice.ObjectiveTo assess temporal trends in ICI use and survival among patients with advanced NSCLC across age strata.Design, Setting, and ParticipantsThis cohort study was performed in approximately 280 predominantly community-based US cancer clinics and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
39
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 49 publications
0
39
1
Order By: Relevance
“…Another important consideration that emerges from the findings of Voruganti et al 5 To our knowledge, this is the first report to assess clinically meaningful survival gains in the era of ICIs in advanced NSCLC across age strata using clinical practice data. The findings from Voruganti et al 5 may help inform shared decisionmaking discussions in clinical practice, particularly for the oldest adult age group with NSCLC.…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…Another important consideration that emerges from the findings of Voruganti et al 5 To our knowledge, this is the first report to assess clinically meaningful survival gains in the era of ICIs in advanced NSCLC across age strata using clinical practice data. The findings from Voruganti et al 5 may help inform shared decisionmaking discussions in clinical practice, particularly for the oldest adult age group with NSCLC.…”
mentioning
confidence: 96%
“…Another important consideration that emerges from the findings of Voruganti et al 5 is how to interpret and apply the survival gains observed in clinical trials to clinical practice, particularly in shared decision-making discussions with adults in the oldest age groups. Clinical trial participants are typically Related article page 334 the fittest of the fit and are less likely to represent the general population of patients receiving cancer treatment in clinical practice.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding who will experience treatment-related side effects is incredibly important, as the number of new cancer drugs is rapidly increasing, with new approvals monthly. Overall survival benefits are improving, yet gains can be modest, particularly among older adults with cancer …”
mentioning
confidence: 99%